Detection of α1 Integrin in Urine of Patients With Immunoglobulin A Nephropathy. (1st March 2008) - Bank, Jonathan; Ben-David, Aharon; Doolman, Ram; Sela, Ben-Ami; Bank, Ilan
Abstract : Background: The α1β1 integrin is a cell surface membrane heterodimer composed of noncovalently linked α1 and β1 polypeptides that is up-regulated on activated and proliferating mesangial cells. Methods: A double-sandwich enzyme-linked immunosorbent assay that detects α1 integrin in a specific and dose-dependent manner at concentrations greater than 150 ng/mL was used to evaluate whether intact α1 polypeptides are secreted in the urine samples of 29 patients with various kidney diseases and in those of 5 healthy individuals. Results: α1 Integrin was detected in 8 of the 29 patients including 3 of 3 patients with biopsy-proven immunoglobulin A nephropathy and 3 of 3 clinically suspected but non-biopsy-proven immunoglobulin A nephropathy with evidence of active nephritis. No α1 integrins were found in samples of 5 healthy controls. Conclusions: α1 Integrin polypeptides can be detected in human urine, particularly in immunoglobulin A nephropathy. Further extensive studies are required to clarify the significance of secretion of α1 integrins in urine of patients with kidney disease.